Gut Dysbiosis Is Associated With the Severity of Cryptogenic Stroke and Enhanced Systemic Inflammatory Response - Zheng, Qianyi; Chen, Yongkang; Zhai, Yanping; Meng, Lin; Liu, Han; Tian, Haiyan; Feng, Renyi; Wang, Jiuqi; Zhang, Rui; Sun, Kedi; Gao, Lina; Wang, Yijing; et al. (Frontiers in Immunology, 2022)
Studies implicate that gut dysbiosis is related with many neurological diseases. However, the potential role of gut dysbiosis in cryptogenic stroke (CS) has not been elucidated yet. In this study, a high prevalence of gastrointestinal (GI) dysfunction and gut inflammation with increased intestinal permeability have been found in CS patients compared with normal controls (NCs). The systemic inflammation in CS patients was also identified by measuring the levels of plasma C-reactive protein (CRP), lipopolysaccharide (LPS), LPS-binding protein (LBP), and white blood cells (WBC) count. Using 16S rRNA sequencing, we found increased alpha diversity, accompanied by a higher abundance of Enterobacteriaceae, Streptococcaceae, and Lactobacillaceae at the family level and Escherichia–Shigella, Streptococcus, Lactobacillus, and Klebsilla at the genus level in the intestinal microbiota of CS patients compared to NCs. Our results showed that the abundance of Klebsilla was positively correlated with the systemic inflammation, the National Institutes of Health Stroke Scale (NIHSS) scores, and the infarct volumes. In conclusion, gut dysbiosis in CS patients was associated with the severity of CS and the systemic inflammation. Maintaining the intestinal homeostasis may be a potential strategy for the treatment of CS.